Olfactory Training Using Heavy and Light Weight Molecule Odors. (March 2017) - Poletti, Sophia C.; Michel, Elisabeth; Hummel, Thomas
Background: Repeated short-term exposure to odors is known to improve olfaction in patients with acquired olfactory dysfunction. The aim was to find out whether differences in molecular weight of odors used for olfactory training influences olfaction. We hypothesized a greater improvement following training with light weight molecule (LWM) odors. Methods: A prospective study was performed in patients with posttraumatic (PTOL) and postviral olfactory loss (PVOL). Olfactory training was performed over a period of 5 months. One group ( n = 48) used four odors containing heavy weight molecules (HWM; >150 g/mol) and another ( n = 48) containing LWM (<150 g/mol). Olfaction was tested before and after the training using the Sniffin' Sticks test. Results: Olfactory training was associated with olfactory improvement, with the improvement in PVOL patients being three times greater than that seen in the PTOL group. Compared with LWM training, HWM training was associated with a significantly greater improvement in Phenyl Ethyl Alcohol (PEA) threshold scores in PVOL patients; however, no such improvement could be shown for other subtests or in PTOL patients. Conclusion: Overall, training was associated with olfactory improvement. With the exception of threshold scores in PVOL, there were no significant differences between LWM and HWM groups.